Sustainable healthcare facilities: Reconciling bed capacity and local needs - Efthimia Pantzartzis; Francis Edum-Fotwe; Andrew Price (2017)
© 2017 The Gulf Organisation for Research and Development Healthcare facilities throughout Europe are constantly changing to support efforts to provide efficient healthcare services with decreasing resources. Recent changes include larger and more specialist hospitals to achieve economies of scale. This approach has yet to be proven to sustainably respond to the demands, and efficiently satisfy the users’ needs. The evidence that supports larger healthcare facilities as more cost effective is limited and contradictory as wider sustainability issues need to be given greater consideration. This information paper presents the findings of a comprehensive literature review that addresses aspects that can lead to sustainable small healthcare facilities. It also establishes sustainable-related factors, including economics and energy efficiency, which could be employed to evaluate the viability of healthcare facilities. A typical small-scale facility provides a case study that contextualises these factors, captures their interdependencies, and explores the viability and sustainability of small hospitals. The findings from the work suggest that small facilities can be viable and more comprehensive research that provides a balanced view of economies of scale is required to support future healthcare design policies, where large and more specialised hospitals may no longer be environmentally, technologically, socially and economically sustainable.